1982
DOI: 10.1111/j.1365-2362.1982.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum thyroglobulin and its autoantibody following subtotal thyroid resection of Graves' disease

Abstract: Thyroid surgery leads to marked changes of the levels of serum thyroglobulin and its autoantibodies in the subsequent 3 postoperative weeks. Furthermore in Graves' disease progression of exophthalmos has sometimes been seen following thyroidectomy. Nineteen medically pretreated patients with Graves' disease and no signs of exophthalmos were studied systematically up to 6 months postoperatively. Nine patients had thyroglobulin antibodies. Mean values rose to 3.5 times pretreatment values within 2 months (P less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…But in some situations following thyroidectomy a combination of persistently increased levels of Tg and TSH with normal thyroid hormones can be seen (33,39). In these cases serum T g values may reflect a consistently increased intraglandular turnover of T g due to incipient failure of Tg synthesis in the thyroid glandular remnant.…”
Section: Serum T G In Patients With Goitre and Thyroid Hormonal Dysfumentioning
confidence: 99%
See 2 more Smart Citations
“…But in some situations following thyroidectomy a combination of persistently increased levels of Tg and TSH with normal thyroid hormones can be seen (33,39). In these cases serum T g values may reflect a consistently increased intraglandular turnover of T g due to incipient failure of Tg synthesis in the thyroid glandular remnant.…”
Section: Serum T G In Patients With Goitre and Thyroid Hormonal Dysfumentioning
confidence: 99%
“…In uztro experiments have shown that irradiation of lymphocytes without antigen availability may augment thyroid autoantibody production (69). However, an increase in serum TgAb concentration is also seen following subtotal thyroidectomy in Graves' disease (33,65). The increasing levels following both kinds of therapy have therefore been explained by release of antigen from the damaged thyroid gland and subsequent temporary change in the homeostatic control of the immune response (33).…”
Section: Serum Thyroglobulin Its Autoantibodies and Thyroid-stimulamentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely documented that surgical thyroidectomy for Graves' disease is followed by a decrease in serum concentrations of Tg, TgAb, and thyroid stimulating immunoglobulins (TSI) (Feldt-Rasmussen et al 1982;Bech et al 1982). Thus, some degree of immune remission seems to follow a reduction in thyroid mass.…”
Section: Discussionmentioning
confidence: 99%
“…Iodinated peptides in Tg as well as iodine-induced apoptosis/necrosis of thyrocytes trigger autoimmune thyroid disease [25]. Increased release of Tg temporarily increases anti-Tg level, and has been reported after thyroid surgery [26], RAI administration [27], and ethanol administration in toxic adenomas [28,29]. In our cases, during the acute phase of SAT, serum Tg levels were increased, whereas anti-Tg was normal, which was followed by development of increased anti-Tg levels 3 months later, with the appearance of GD.…”
Section: Discussionmentioning
confidence: 99%